What made Proto-Germanic *jah ’and’ an infinitive marker in westernmost Uralic? Observations from the Saami-Scandinavian border - Ylikoski, Jussi (Norsk Lingvistisk Tidsskrift, 2017)
The paper provides an account of a previously neglected infinitive marker in South Saami. Originally recognized by Bergsland (1946), later descriptions of South Saami have disregarded the use of the coordinating conjunction jih ’and’ as what appears to be a largely optional infinitive marker preceding the infinitive in -dh. On the basis of actual language data going back to the 1880s, it is shown that jih has been used as an infinitive marker in various dialects for over a century. Special attention is given to the unprecedented development of the infinitive marker from a coordinating conjunction. The use of jih has been modeled by the Norwegian/Swedish conjunction og/och /É”/ ’and’ and the homophonous infinitive marker å/att /É”/. The paper discusses the development and reception of the infinitive marker from contact-linguistic and typological perspectives. The diachrony and synchrony of the coordinating-cum-infinitival morpheme also provides new perspectives to the corresponding morphemes in Scandinavian.